Gender differentials and old age survival in the Nairobi slums, Kenya - Bennett, Rachel; Chepngeno-Langat, Gloria; Evandrou, Maria; Falkingham, Jane (Social Science & Medicine, 2016)
This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in the slums do not have better survival. The conventional female advantage in mortality only becomes apparent after accounting for the cumulative influence of individual characteristics, social networks, health and socio-economic status, suggesting the female advantage in unadjusted old-age mortality does not apply to contexts where women experience significant disadvantage across multiple life domains. This highlights the urgent need to redress the support, status and opportunities available for women across the life course in contexts such as the Nairobi slums. In addition, a greater number of factors differentiate mortality risk amongst men than amongst women, suggesting inequality amongst slum dwelling older men and highlighting the need for gender sensitive interventions which account for the particular needs of both genders in old age.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; bidonvilles; environnement; inégalités; kenya; personnes âgées; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques